Prioritizing Conservation Areas for the Hyacinth Macaw (Anodorhynchus hyacinthinus) in Brazil From Low‐Coverage Genomic Data - Sibelle Torres Vilaça; Jeronymo Dalapicolla; Renata Soares; Neiva Maria Robaldo Guedes; Cristina Y. Miyaki; Alexandre Aleixo (Evolutionary Applications)
ABSTRACT Estimates of current genetic diversity and population connectivity are especially important for endangered species that are subject to illegal harvesting and trafficking. Genetic monitoring can also ensure that management units are sustaining viable populations, while estimating genetic structure and population dynamics can influence genetic rescue efforts and reintroduction from captive breeding and confiscated animals. The Hyacinth Macaw (Anodorhynchus hyacinthinus) is a charismatic endangered species with a fragmented (allopatric) distribution. Using low coverage genomes, we aimed to investigate the dynamics across the remaining three large disjunct populations of Hyacinth Macaws in Brazil to inform conservation strategies. We obtained low coverage DNA data for 54 individuals from seven sampling sites. Our results showed that Hyacinth Macaws have four genetically structured clusters with relatively high levels of diversity. The Pantanal biome had two genetically distinct populations, with no obvious physical barriers that might explain this differentiation. We detected signs of gene flow between populations, with some geographical regions being more connected than others. Estimates of effective population size in the past million years of the species' evolutionary history showed a decline trend with the lowest Ne in all populations reached within the last few thousand years. Our findings suggest that populations from the Pantanal biome are key to connecting sites across its distribution, and maintaining the integrity of this habitat is important for protecting the species. Given the genetic structure found, we also highlight the need of conserving all wild populations to ensure the protection of the species' evolutionary potential.